MAKNA DAN PENGGUNAAN VERBA ‘MEMBANTU’ DALAM BAHASA JEPANG SEHARI-HARI: TINJAUAN SEMANTIK - I Wayan Wahyu Cipta Widiastika (SPHOTA: Jurnal Linguistik dan Sastra, 2021)
Japanese is a foreign language that has many variations of the lexicon. One of them is the lexicon variation in verbs. This study discusses the meaning and use of verb 'help' in everyday Japanese conversation. The data is in the form of sentences used by native Japanese speakers. Data collection was carried out through interviews and note taking techniques. The data were analyzed using the contextual meaning theory approach of Pateda, (2010 : 116). The result shows that there are eight variations of the verb 'help' in Japanese namely: tetsudau, tasukeru, osewa ni naru, sukuu, kyuujo suru, enjo suru, kifu suru, and ouen suru. From the analysis, the verb "tetsudau" means helping someone to complete an activity that has not been completed. The verb 'tasukeru, sukuu and kyuujo suru' means to help or save someone who is experiencing difficulty or danger. Then, the verb 'osewa ni naru' means to help someone by providing guidance, kindness or facilities. The verb 'enjo suru' means to help by making things easier. The verb "ouen suru" means to help by providing support or encouragement. And finally, the verb "kifu suru" means to help someone by giving something in the form of an object (money). Abstrak Bahasa Jepang merupakan salah satu bahasa asing yang mempunyai banyak variasi leksikon. Salah satunya adalah variasi leksikon dalam verba. Dalam jurnal ini membahas mengenai makna dan penggunaan verba 'membantu' dalam percakapan bahasa Jepang sehari-hari. Data dalam jurnal ini berupa kalimat-kalimat yang digunakan oleh penutur asli bahasa Jepang. Pengumpulan data dilakukan melalui wawancara dan teknik catat. Data dianalisis dengan pendekatan teori makna kontekstual Pateda, (2010:116). Dari data yang telah ditemukan, verba ‘membantu’ dalam bahasa Jepang ada delapan variasi, yaitu: tetsudau, tasukeru, osewa ni naru, sukuu, kyuujo suru, enjo suru, kifu suru, dan ouen suru. Dari hasil analisis, verba ‘tetsudau’ bermakna membantu seseorang untuk menyelesaikan sesuatu aktivitas yang belum selesai. Verba ‘tasukeru, sukuu dan kyuujo suru’ bermakna menolong atau menyelamatkan seseorang yang sedang mengalami kesulitan atau bahaya. Kemudian, verba ‘osewa ni naru’ bermakna membantu seseorang dengan memberikan bimbingan, kebaikan, atau fasilitas. Verba ‘enjo suru’ bermakna membantu dengan mempermudah menyelesaikan sesuatu. Verba ‘ouen suru’ bermakna membantu dengan memberikan dukungan atau semangat. Terakhir, verba ‘kifu suru’ bermakna membantu seseorang dengan memberikan sesuatu berupa benda (uang).